Vlogger's persuasive strategy and consumers' purchase intention: The dual mediating role of para-social interactions and perceived value - Sheng, Xiayan; Zeng, Zhenhua; Zhang, Wen; Hu, Yuanhui (Frontiers in Psychology, 2022)
It is a new advertising marketing method for commodity companies to use vloggers to endorse their products, and to influence consumers' attitudes and decisions. In view of this phenomenon, there are few studies on the relationship between vloggers and consumers, and this study aims to explore how the persuasive strategies used by vloggers to promote products influence consumers' purchase intentions. Based on the concepts of Aristotle's persuasion theory, this study extracts two specific persuasive approaches, “two-sided messages” and “emotional appeal,” to explore consumers' perceptions of them and the effectiveness of these two strategies. At the same time, para-social interaction and perceived value as intermediary factors are also included in the study for further discussion. The study empirically analyzed a sample of 511 questionnaires from participants who had purchased products recommended by vloggers and came to the following conclusions: (1) vloggers can enhance consumers' purchase intention by adopting two-sided messages persuasion when promoting products; (2) vloggers' emotional persuasion can enhance consumers' purchase intention; (3) as an intermediary variable, para-social interaction plays a more obvious role in vloggers' persuasion by appealing to emotions. The audience can have common feelings with vloggers, and they are more connected with each other, thus increasing their willingness to buy; (4) Perceived value, as an intermediary variable, plays a more obvious role in vloggers' persuasion with the two-sided messages. The two-sided messages can show vloggers' credibility and more abundant information about products, so that consumers have a positive perception of product value, and the direct persuasion effect of the two-sided messages is greater. Based on the results of the study, this paper helps vloggers to adopt different persuasive approaches for different types of audiences, choose the proper marketing methods, attract the potential customers, and achieve such purposes as enriching product marketing forms and increasing market share.